The Pengaruh Model Pembelajaran Berbasis Masalah dan Sikap pada Fisika terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik - Riskha Lestari Sadiah; Muh. Sidin Ali; Khaeruddin (Jurnal Penelitian Pendidikan IPA, 2025)
One of the student's abilities that needs to be improved in learning is problem-solving ability. However, in reality, students' problem-solving abilities are still relatively low, especially in physics subjects. This study aims to analyze the effect of learning models and attitude in physics on the problem solving. This research is a true experiment with a 2x2 factorial design. The population is all class X SMA Negeri 7 Luwu Utara years 2022/2023. The sample of two classes using simple random sampling techniques. Methods of data collection using attitude questionnaire on physics and physics problem-solving skill tests. Data analysis using two-way ANOVA The results showed that: There were differences in the physics problem-solving skills of students who were taught using problem-based learning models and those who were taught using discovery learning models, for attitudes to high physics, there were differences in problem-solving skills physics taught using problem-based learning models with those taught using discovery learning models, for low physics attitudes, there are differences in the physics problem-solving skills of students who are taught using problem-based learning models with those taught using discovery learning models, and there is no interaction between the learning model and attitudes toward physics on students' physics problem-solving skills.